UMP associates internalise Rukun Negara as key for unity - Nur Hartini, Mohd Hatta (2020)
Pekan, 26 August 2020 - ‘A pipe shapes flowing water, consensus shapes flowing words’, that is the old adage that Malaysians need to hold in maintaining national harmony and unity.